Money priming and social behavior of natural groups in simple bargaining and dilemma experiments - Julija Michailova; Christoph Bühren (Philipps-University Marburg, School of Business and Economics, 2015)
We examine the effects of money priming and solidarity on individual behavior in three simple experiments: dictator game, ultimatum game, and prisoner's dilemma. Our study comprises two money treatments and two neutral (control) treatments. Additionally, we control for the strength of social ties between experimental participants. Although our priming procedure is sufficient to remind people of the concept of money, it is not sufficient to induce systematically different behavior of the treatment groups compared to the control groups. Moreover, we do not find any significant differences between groups with strong vs. weak social ties. Since our findings contradict previous research, it calls for further investigation on the topic of how money priming influences economic behavior.
Keywords: C78; C9; D36; 330; money priming; bargaining; dilemma; social behavior; natural groups; economic experiment